APPLICATION OF TOTAL QUALITY MANAGEMENT IN PUBLIC SECONDARY SCHOOLS IN DISTRICT GUJRAT - Sumaira Asghar; ul Islam, Dr. Mubeen; Zaman, Dr. Sher Muhammad (JELM, 2025)
The standard and quality of the education system have been one of the biggest worries. The quality of a country's education is very important for its growth. The goal of TQM as a management philosophy and practice is to make the best use of an organization's people and things to reach its goals. The study was done to examine the implementation of Total Quality Management (TQM) in public secondary schools within the Gujrat district. The study was directed by three research questions and one null hypothesis. A descriptive survey methodology was utilized. The population comprised all 318 public secondary schools in Gujrat. A multi-stage sample method was utilized to choose 100 people to participate in this study. This group included 25 headmasters, 25 deputy headmasters, and 50 teachers. A self-constructed instrument questionnaire was utilized for data collection. To guarantee the content validity of the instrument, the perspectives of seven specialists from the Education Department at the University of Gujrat were solicited. To answer the three research objectives, the researcher used descriptive statistics, the mean, and the standard deviation. Simultaneously, the null hypothesis was evaluated utilizing inferential statistics ANOVA at a 0.05 significance level. The study's findings indicated that the “total commitment” was partially implemented in the administration of secondary schools. The results demonstrated partially implementation of good communication and collaboration. This means that TQM is only used a little bit in the Gujrat district. Some suggestions were given, such as that QAED should set up seminars, workshops, conferences, and training sessions for school staff to talk about TQM traits. Headmasters should be completely dedicated to using the TQM principles to run their schools well. This way, quality education goals may be achieved.